Analysis of the Completeness of Procedures of Ventolin Inhaler Usage Through the Use of Video on Asthma Patients of Probolinggo Hospital - Godeliva Adriani Hendra; Martanty Aditya; Chresiani Destianita Yoedistira (LPPM Universitas Ma Chung, 2021)
Asthma is an obstructive chronic pulmonary disease which causes shortness of breath and requires distinct diagnostic strategies and treatment management. The disease requires long-term treatment where the patient's condition can hopefully remain under control. There are still many symptom recurrences found in asthma patients due to inaccurate/incomplete procedures in using inhalers. The purpose of this community service is to develop knowledge and understanding of the completeness of usage procedures of Ventolin Inhalers by utilizing videos as visual training to achieve expected therapeutic effect and aid asthma patients in controlling/avoiding asthma relapse. Data collection was carried out through observation in the form of checklists which contained the procedures for using the inhaler, followed by descriptive analysis. The observations were made one month before and after video education. Education in video format was distributed on day one. The video was uploaded to Youtube and contain procedures on how to use the inhaler device. Alternatively, it can also be sent through the patient's WhatsApp account. The data collection process was carried out from April to July 2020. There were changes in the number of patients before and after the provision of video education. This shows the level of knowledge and understanding of asthma patients regarding the completeness of the procedure for using Ventolin Inhaler had increased. Inappropriate usage of inhalers or errors made during the implementation of each step can affect the effectiveness of drug therapy and can cause unwanted side effects.